Grief labour on Instagram: Resilient influencers and platformed grief - HARJU ANU A.; PENTIKÄINEN LINDA (Nordic Journal of Media Studies)
Drawing on the postfeminist notion of resilience, in this article we explore female influencers in grief who, after losing their spouse, share their practices of grieving on Instagram. We examine how, in the narrations of grief, the grieving self is constructed as a resilient subject able to move forward in the “grief journey” through exercising control at the site of the self. The article shows how reconciling the strain of coping with loss with influencer culture and platform requirements demands significant affective labour. We argue that such grief labour, a concept we introduce in this article, is rooted in the neoliberal regime of control targeted at the self. Utilising a digital media ethnographic design and multimodal content analysis, this study sheds light on influencers’ complex affective practices of resilience in the context of death; furthermore, the study advances knowledge on the normative aspects of platformed grief and further elaborates on the commercialisation of personal grief in the current platform economy.